2011
DOI: 10.1111/j.1365-2044.2011.06658.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of connexin36 gap junctions in modulating the hypnotic effects of isoflurane and propofol in mice

Abstract: SummaryGap junction blockade is a possible mechanism by which general anaesthetic drugs cause unconsciousness. We measured the sensitivity of connexin36 knockout mice to the hypnotic effects of isoflurane and propofol. The experimental endpoint was recovery of the righting reflex of the anaesthetised animals during 0.2% step-reductions in isoflurane concentration, or following intraperitoneal injection of propofol (100 mg.kg). Connexin36 knockout animals were more sensitive to the hypnotic effects of isofluran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The fluranes, however, are all ethers and are expected to have different mechanisms of action. One mechanism of action of isoflurane and sevoflurane is the modulation of gap junction mediated signaling . It is also reported that different length perfluorinated compounds can inhibit gap junction intercellular communication .…”
Section: Discussionmentioning
confidence: 99%
“…The fluranes, however, are all ethers and are expected to have different mechanisms of action. One mechanism of action of isoflurane and sevoflurane is the modulation of gap junction mediated signaling . It is also reported that different length perfluorinated compounds can inhibit gap junction intercellular communication .…”
Section: Discussionmentioning
confidence: 99%
“…This theory, underpinned by the “Meyer‐Overton correlation”, held for about 80 years, until it was refuted in the late 80s by elegant experiments indicating that the targets must involve proteins pockets because general anesthetics are stereospecific . Since then, every molecular mechanism seems to have been proposed for general anesthesia, from nonspecific effects on various proteins to specific channel targets to gap junctions and microtubules . Accordingly, general anesthetics appear to impair the function of a wide range of molecules, as determined by in vitro assays , although it is now generally accepted that GABA A receptors represent a major target for most of these drugs .…”
Section: Sleep and Synaptic Mechanisms Together May Explain General Amentioning
confidence: 99%
“…Thus the knockout experiments, together with a subset of the pharmacological experiments, suggest that interneuronal gap junctions may be protective against seizure, and that their ablation can enhance pathological excitability. There are also data that suggest that Cx36 knockout mice are more sensitive to the hypnotic effects of anesthetic drugs (Jacobson et al 2011).…”
Section: Introductionmentioning
confidence: 99%